The ethics of believing in God - Mawson, TJ (Cambridge University Press, 2010)
In this paper, I aim to discuss not the issue of whether or not we do in fact have reasons to suppose that there is or that there is not a God, but rather an issue which looks at first glance like it might have a certain methodological priority, the issue of what is the right ‘ethics of belief’ for belief in God: should one believe in God only if one has positive reasons in favour of doing so or is it permissible to believe in Him without such reasons? In this paper, I want to see what can be done to decide which of the various options for an ethics of belief in God is right prior to deciding whether or not God exists. Let's start then by getting these options out onto the table. One of them is as follows: 1) We should believe in God only if we have positive reasons to do so.